2012
DOI: 10.5194/acpd-12-5065-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gaseous VOCs rapidly modify particulate matter and its biological effects – Part 1: Simple VOCs and model PM

Abstract: This is the first of a three-part study designed to demonstrate dynamic entanglements among gaseous organic compounds (VOC), particulate matter (PM), and their subsequent potential biological effects. We study these entanglements in increasingly complex VOC and PM mixtures in urban-like conditions in a large outdoor chamber. To the traditional chemical and physical characterizations of gas and PM, we added new measurements of gas-only- and PM-only-biological effects, using cultured human lung cells as model in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…Measurements from both gas and particle phases were taken periodically until sunset. Detailed operating conditions for chemical and physical monitoring of the chamber have been previously described (44). To detect gaseous MAE formation, chamber air was continuously drawn through two fritted-glass bubblers in series at a sampling flow rate of ∼1 L·min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Measurements from both gas and particle phases were taken periodically until sunset. Detailed operating conditions for chemical and physical monitoring of the chamber have been previously described (44). To detect gaseous MAE formation, chamber air was continuously drawn through two fritted-glass bubblers in series at a sampling flow rate of ∼1 L·min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…In vitro exposures were performed using the GIVES (gas in vitro exposure system) as previously described (Doyle et al, 2007;Ebersviller et al, 2012;Rager et al, 2011a;Sexton et al, 2004). Briefly, cells were grown on 30 mm Millicell membranes (EMD Millipore Corp., Billerica, MA) in F12-K media with 10% fetal bovine serum (FBS) plus 0.01% penicillin/streptomycin at a density of 850 000 cells/ membrane, 28 h prior to exposure as described (Jaspers et al, 1997;Zavala et al, 2014).…”
Section: Cell Culture and Exposurementioning
confidence: 99%
“…Its strong reactivity and tendency to generate free radicals, such as hydroxyl (OH) radicals and reactive odd nitrogen species (NO y ), cause damage to a wide range of cellular components (Byvoet et al, 1995;Cataldo, 2006a;Jorge et al, 2002;Weschler et al, 1992). Furthermore, O 3 is created as a byproduct of VOC photolysis and oxidation, degradation of chlorine and nitrogen compounds, and surface reactions on particulate matter (PM) (Crounse et al, 2012;Doyle et al, 2004;Ebersviller et al, 2012;Faxon & Allen, 2013;Meng et al, 1997;Weschler et al, 1992). In addition, it is wellknown that photochemical reactions in air pollution mixtures generate higher levels of O 3 and secondary oxidative compounds (Doyle et al, 2007), an effect which may increase with global climate change (Jacob & Winner, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A surrogate aerosol to diesel particles was designed to be non-toxic but of similar size and density (aerosolised mineral oil). By conducting a series of experiments where mixing in a dark chamber a non-toxic aerosol of mineral oil with a single toxic gas species, it was demonstrated that the non-toxic mineral oil could be made significantly toxic [73] (Fig. 10).…”
Section: Expansion Of the Research Group And Chambers To Test Combustmentioning
confidence: 99%
“…Demonstration using a paired gas-only cellular exposure (left) and a particle-only cellular exposure system (right) of a gas-phase toxicant (Tolald, p-tolualdehyde) (left C) making a non-toxic particle (MOA, mineral oil aerosol) (right B, C) become highly toxic to cells (right D). [73,74] Conditions: A are clean air exposures; B are clean air and non-toxic particle; C are gas-phase toxicant, no particles exposure, and D are mixture of gas-phase toxicant and non-toxic particle followed by exposure. Note that in exposure D on left, the gas-phase only toxicity has decreased due to much of the gas-phase toxicant having moved to the particle.…”
Section: Expansion Of the Research Group And Chambers To Test Combustmentioning
confidence: 99%